PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO DI KOTA KENDARI - Lery, Mega; Zaid, Sudirman; Isalman, Isalman; Panjaitan, Feliks Anggia Binsar Kristian; Taufik, Muh (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2024)
This study aims: (1) To determine the effect of brand image, price, and product quality of Oppo Smartphone users in Kendari City. (2) To determine the effect of brand image of Oppo Smartphone users in Kendari City. (3) To determine the effect of the price of Oppo Smartphone users in Kendari City. (4) To determine the effect of user product quality Oppo Smartphone ini Kendari City. The population in this study is all Kendari City residents who buy and use Oppo Smartphone products themselves, while the sample is 80 respondents using the Hair formula. The data collection method is using a questionnaire. This research technique uses multiple regression analyses. The results of this study indicate that: (1) Brand image has no significant effect, while price and product quality have a positive and significant effect on purchasing decision. (2) Brand image has no significant postive effect on purchasing decisions. (2) Price has a significant positive effect on purchasing decisions. (3) Product quality has a significant positive effect on purchasing decisions.